Theoretical energies and radiative transition parameters of W L. (August 2019) - Chen, Z.B.; Tian, Y.S.; Sang, C.C.; Wang, H.J.
Abstract: Using fully relativistic multiconfiguration Dirac-Fock (MCDF) wavefunctions in the active space approximation, the energy levels, lifetimes, radiative rates, and oscillator strengths are determined for transitions in Mn-like W L ion. For the calculations, Breit interaction (BI) and quantum electrodynamics (QED) corrections to the levels are estimated in extensive relativistic configuration interaction (RCI) procedure, and results are reported for all electric dipole (E1), electric quadrupole (E2), magnetic dipole (M1), and magnetic quadrupole (M2) transitions among the lowest 121 levels, belonging to the 3 s 2 3 p 6 3 d 7, 3 s 2 3 p 5 3 d 8, 3s3 p 6 3 d 8, 3 s 2 3 p 4 3 d 9, and 3s3 p 5 3 d 9 configurations. Comparisons are made with similar data obtained with FAC (Flexible Atomic Code) to assess the accuracy of the results. The present results are also assessed by comparison with the data compiled by the Atomic Spectra Database (ASD) of National Institute of Standards and Technology (NIST) and other existing theoretical/experimental ones for few levels in literature showing an overall good agreement. i.e., the energies agree within 0.5% with the experimental results, and the M1 transition rates agree within 5% with other theoretical results. Beside the ground configuration, almost all atomic parameters presented in this work are calculated for the first time and thus significantly increases the amount of accurate data for W L ion. Our results should be beneficial in future for identification of spectral lines, in plasma modelling, and in fusion plasma research.